Prof. Dr. Ali Selcuk Biricik's Professional Life and his Contributions to the Geography Science - (:unkn) unknown (MARMARA UNIV, 2015)
Having retired from the Department of Geography, Faculty of Science and Letters of the Marmara University in 2013, Prof. Dr. Ali Selcuk Biricik has been one of the esteemed lecturers very well known by the world of geography with his professional life that lasted almost half a century, and made significant contributions to the science of geography in many fields. This paper deals with Biricik's educational background, professional life, scientific personality, contributions to the geography education, administrative and academic functions briefly, and his scientific publications have been introduced with clear identifications. Undoubtedly, he will continue to conduct studies in different parts of our country, and in various fields of the science of geography, and to be together with his colleagues and students. As a matter of fact, even though he has retired, the fact that he continues his studies with the same passion is the indication of his respect towards his profession and love for geography.
Keywords: Prof. Dr. Ali Selcuk Biricik; geography; Marmara University